2019
DOI: 10.5530/ijopp.13.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Finasteride in the Management of Androgenetic Alopecia in Male: A Narrative Review

Abstract: The purpose of this review was to evaluate the role of finasteride, a type-II 5α-reductase inhibitor in the prevention and treatment of androgenetic alopecia (AGA) in males. Finasteride inhibits 5α-reductase and reduce the biosynthesis of dihydrotestosterone (DHT). This inhibition marks a decrease in concentration of DHT and provides a novel and selective approach to androgen deprivation. Clinical trials have proven the safety and efficacy of tablet finasteride 1 mg for AGA. In this review, we discuss all aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…1,56 Finasteride does not affect T levels or binding of DHT to AR and therefore does not possess androgenic, antiandrogenic, estrogenic or antiestrogenic, or progestational or steroid hormone-related properties. 56,57 Pharmacokinetics Finasteride when taken orally has a mean half-life of approximately 6 hours, mandating a daily dosage to maintain uniform blood levels. Extensive hepatic metabolism is by the cytochrome P450 enzyme system, specifically CYP3A4 enzyme subfamily.…”
Section: What We Know About Androgens and Mphlmentioning
confidence: 99%
See 4 more Smart Citations
“…1,56 Finasteride does not affect T levels or binding of DHT to AR and therefore does not possess androgenic, antiandrogenic, estrogenic or antiestrogenic, or progestational or steroid hormone-related properties. 56,57 Pharmacokinetics Finasteride when taken orally has a mean half-life of approximately 6 hours, mandating a daily dosage to maintain uniform blood levels. Extensive hepatic metabolism is by the cytochrome P450 enzyme system, specifically CYP3A4 enzyme subfamily.…”
Section: What We Know About Androgens and Mphlmentioning
confidence: 99%
“…Although various dosages ranging from 0.01 mg to 5 mg/day have been tried, 1 mg dosage has been found to be optimal. 57 Finasteride has level 1 evidence for efficacy to prevent progression and improve hair loss in MPHL. 1,4,19,20,32,54,[56][57][58][59] Studies have revealed that the hair count and weight start show increase by approximately 6 months and the improvement continues at least for up to 5 years.…”
Section: What We Know About Androgens and Mphlmentioning
confidence: 99%
See 3 more Smart Citations